Reconstruction of lateral attic wall in acquired cholesteatoma - Erdoglija, Milan; Milojević, Milanko; Grgurević, Uglješa; Sotirović, Jelena; Milanović, Nada; Cerović, Snežana; Jović, Milena; Baletić, Nenad (Vojnosanitetski pregled, 2017)
Background/Aim. Attic cholesteatoma is an epithelial cystic pseudotumor which arises in the top compartment of the middle ear. Surgery is the only therapeutic treatment for attic cholesteatoma. The aim of this study was to analyze the surgical and audiological results in tympanoplasties that use a logical application of several techniques for the management of attic cholesteatoma. Our hypothesis was that the tympanoplasty technique with cartilage/bone reconstruction of the achieve better outcome than the tympanoplasty technique with only temporal fascia reconstruction of the lateral attic wall. Methods. This retrospective clinical study included 80 patients, aged 16–65 years, with attic cholesteatoma undergoing canal “wall up” tympanoplasty with lateral attic wall reconstruction, under general anesthesia in the Eear, Nose and Throat Clinic, Military Medical Academy in Belgrade between 2006 and 2010. The patients were divided into two groups according to the type of lateral attic wall reconstruction: the group I of 60 patients with cartilage/bone plus temporalis fascia lateral attic wall reconstruction and the group II of 20 patients with only temporal fascia lateral attic wall reconstruction. Postoperative follow-up examinations were done at least 5 years after the surgery. The χ2 test was used to compare postoperative sequelae for two groups of operated patients with lateral attic wall reconstruction. The independent and paired samples t-test of air conduction and air-bone gap were used to compare the results of preoperative and postoperative hearing tests. Results. The differences between hearing measurements of the two groups according to preoperative and postoperative auditory thresholds of the air conduction and the air-bone gap were considered no statistically significant. The difference between the two groups recarding to recurrent attic retraction pocket appearance and recurrence of cholesteatoma was considered statistically significant and the results were much better in the group I of the operated patients with cartilage/bone lateral attic wall reconstruction. Conclusion. “Wall up” tympanoplasty for attic cholesteatoma with lateral attic wall reconstruction leads to good anatomical and audiological results. A significant hearing improvement was obtained in both the types of lateral attic wall reconstructions in this study. Reconstruction with cartilage or mastoid cortex bone showed favorably long-term functional and anatomical results compared to primary tympanoplasty using only temporal fascia for lateral attic wall reconstruction in cases of attic cholesteatoma.